Possibilities and forms internationalisation of business services - Majchrzak, М.; Niedzielski, P. (Видавництво Львівської політехніки, 2013)
Due to technological progress, business services have a significant share in exports and imports of services. About 30% of business service providers provide them off-site location, which means that direct contact with the recipient service provider for these services is not necessary. Availability and better services for business means that many companies are choosing to externalizing large part of the services entrusted them shared service centers. У зв'язку з технічним прогресом бізнес-послуги мають велику частку в експорті та імпорті послуг. Близько 30 % постачальників бізнес-послуг надають їх «на відстані», що означає, що прямий контакт з постачальником сервісу для одержувачів цих послуг не є необхідним. Існуюча і краща якість послуг для бізнесу означає, що багато компаній екстерналізують велику частину послуг, які їм доручені, до спільних сервісних центрів.
Можливості і форми інтернаціоналізації бізнес-послуг
Keywords: business services; internationalization of services; shared services centers; бізнес-послуги; інтернаціоналізація послуг; спільні сервісні центри